Systems engineering interventions in healthcare services and systems – a systematic review and framework development - Yuan Yin; Thomas Richards; Ji Han; Saeema Ahmed-Kristensen (BMC Health Services Research, 2026)
Abstract Background Systems design approaches show promise towards increasing efficiency and reducing costs for health systems and services, while preserving patient experience and health outcomes. However, their application has so far been limited. Objectives This review aims to: (1) identify the state of the art systems engineering and design approaches applied to healthcare services and system, (2) develop a conceptual framework that explains how these approaches relate to each other across micro (patient), meso (service), and macro (system) levels, and (3) provide practical guidance on selecting and combining approaches for different healthcare scenarios. Methods The inclusion criteria were reviews of systems engineering methodologies that have been applied at a systems-level in a healthcare context, including quantitative or qualitative secondary studies such as reviews, systematic reviews, overviews, meta-analyses, and meta-syntheses. Primary studies, or studies using systems engineering methodology towards specific interventions (such as healthcare apps) rather than health services/systems, were excluded. Eleven databases were searched (Embase, HMIC, Medline, PsycInfo, SPP, AgeLine, AMED, CDAS, CINAHL, SCOPUS, WoS) on 04/11/2024 for reviews published within the previous five years. The risk of bias/quality assessment tools used applied in the included reviews was listed. A framework synthesis methodology was applied to extract data according to a framework developed a priori. Results After removing duplicates, we screened 1752 papers. 62 were sought for full text retrieval, while 57 were available. Finally, after screening for eligibility, we included 32 reviews that involve a total of 1127 studies. Our synthesis reveals that systems engineering and design methodologies have been increasingly applied in healthcare service contexts, with service design, service improvement, and service development as the most common areas of focus. User-centred design and co-design approaches have enabled more inclusive and patient-responsive service frameworks, while systems approaches have provided tools for managing complexity at policy and organisational levels. Distinctions among sub-methodologies (such as the degree of structure, depth of user engagement, and level of system intervention) highlight the importance of aligning methodological choice with healthcare context and stakeholder needs. Despite growing adoption, significant gaps remain in outcome standardization, implementation evaluation, and adaptation for low-resource or culturally diverse settings. Based on these findings, a conceptual framework was developed to map how systems engineering and design methodologies operate across micro (individual), meso (service), and macro (system) levels of healthcare. The framework highlights that system-level change requires systems thinking combined with stakeholder engagement, whereas patient-level improvement is supported by design thinking as well as patient-engaged co-design approaches that do not necessarily follow a formal design thinking process. Conclusions This review shows that different methodologies offer distinct strengths across different levels of healthcare. User-centred design and co-design approaches are most effective for addressing patient-level challenges, enhancing usability, engagement, and experiential outcomes. In contrast, system-level transformation requires systems thinking and structured stakeholder engagement to manage complexity and support sustainable organisational and policy change. The promoted conceptual framework advances understanding of how to match methodological choice to context and contributes a foundation for more integrated, patient-centred, and system-responsive healthcare improvement.